Os Tupinambá no Brasil colonial: aspectos da transmissão musical - OLIVEIRA, Rafael Severiano de (Universidade Federal do Pará, 2017)
Ethnomusicology study on which I was searching for understanding, from the historical reports, on the aspects of musical transmission of Tupinambá society on colonial Brazil. Studies about this society demonstrate that a diverse cultural knowledge were kept and transmitted by ritualistic practices that occurred on the society. These practices were, by the time, beyond celebrations, the moment which a set of knowledge was transmitted to the younger generations by the old ones, being a circulation and appreciation locus of knowledge: the older generations taught the younger ones to follow a social model. The knowledge transmission also occurred in social everyday life. Both cases the traditional knowledge appropriation didn’t imply the absence of creation and recreation of this knowledge. The assumption is that musical knowledge was transmitted in the same way: on ceremonial, ritual and everyday practices. The methodology consisted on analysis of historical accounts interpreted in the light of assumptions of Ethnomusicology, Education and Ethnology, and a wide context of the various contexts of society above all the musicals, which I called musical contexts. The assumption is that musical knowledge was transmitted in the same way: ritual social and everyday practices. The methodology consisted in analysis of historical accounts interpreted in the light of assumptions of Ethnomusicology, Education and Ethnology, and a wide context of the society in question, especially the contexts I have called the musical contexts. The time frame focus on the XVI and XVIII centuries, period which the principal fonts were produced. As a contribution, it’s intended to increase knowledge of the Tupinambá, especially on musical aspects, as well as contribute to the Ethnomusicology of indigenous societies of lowland South America. The conclusions reached by this work point that musical transmission occurred on cerimonial, ritual and everyday practices, and presenting aspects of this transmission.